Play hard, study hard? The influence of gamification on students’ study engagement - Chen, Jun; Liang, Mo (Frontiers in Psychology, 2022)
In recent years, gamification is widely used in the education. In this article, we build one theoretical model to illustrate how gamification influences students’ study engagement. To examine our hypotheses, we distributed our questionnaire surveys to 187 students from one university of China. Correlational analyses, regression analyses and confirmatory factor analyses were used to test our hypotheses. The results show that gamification influences students’ study engagement through the indirect effects of enjoyment and self-efficacy. Implications and future research directions are discussed.